Benefits measurement of a plan to reduce hypertension in a healthcare foundation using the BCTool - Pereira, L. (2021)
The hypertension is a well know problem and associated with a high salt consuming is one of the commonest chronic diseases.To measure the impact of this consuming it has been applied the methodology provided by the Business Case tool (BC Tool), in a Portuguese foundation for elderly, in order to contribute for Intervention Plan for the reduction of hypertension which aims to reduce salt consumption in the Portuguese population and to improve the control of Hypertension through a phased reduction in salt consumption.This objective has been achieved by changing the availability of foods with lower salt contents and by decreasing the addition of salt in cooking. The results of these measures provided a substantial benefit in terms of Benefits Measurements and Cost Analysis besides the results of SROI measurement in order to obtain the social benefits of this initiative of the Intervention plan to reduce hypertension. Along these results it has been collected the suggestions for improvements that would allow the Sarah Beirão Foundation's response to the needs of its users to be improved.